KISAH ISTRI-ISTRI NABI IBRAHIM AS PERSPEKTIF PENDIDIKAN ISLAM - Abd Rozaq; Suliyanto Suliyanto (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2020)
Islamic education refers to the development of future human life without eliminating Islamic principles mandated by Allah SWT to humans. Therefore, we need to emulate and imitate the life of the Prophet Ibrahim and his family to be used as materials in delivering Islamic religious education ways. The focus of this research are: (1) the concept of Islamic education and the story of wives of Prophet Ibrahim AS. (2) The purpose of Islamic education in the story of the Wives of the Prophet Ibrahim. (3) Mirror of Islamic educational material in the story of the Wives of the Prophet Ibrahim. (5) Evaluation of Islamic education in the story of the Wives of the Prophet Ibrahim. This research is based on literature review. The results of the study: Prophet Ibrahim AS educated and preached to all walks of life as well as with various types and backgrounds. His followers are children, wives and parents, then the surrounding community. The attributes of education that can be taken from the Prophet Ibrahim, among others: obedient to Allah SWT, hanif, honest (shiddiq), trustful and intelligent (high knowledge), patient, gentle feelings. The lesson learns taught by the Prophet Ibrahim are monotheism (aqeedah), moral conduct, worship and tazkiyatun nufus. The methods used by the US Ibrahim in presenting the study are: the exemplary method (uswatun hasanah), the advice method, the dialogue method and the argument method.